Imine-based [2]catenanes in water. Issue 5 (3rd January 2018) - Caprice, Kenji; Pupier, Marion; Kruve, Anneli; Schalley, Christoph A.; Cougnon, Fabien B. L.
Abstract : The hydrophobic effect promotes the self-assembly of imine-based [2]catenanes in pure water. Abstract : We report the efficient condensation of imine-based macrocycles from dialdehydeA and aliphatic diaminesB n in pure water. Within the libraries, we identified a family of homologous amphiphilic [2]catenanes, whose self-assembly is primarily driven by the hydrophobic effect. The length and odd-even character of the diamine alkyl linker dictate both the yield and the conformation of the [2]catenanes, whose particular thermodynamic stability further shifts the overall equilibrium in favour of imine condensation. These findings highlight the role played by solvophobic effects in the self-assembly of complex architectures.